PEMANFAATAN TEPUNG BIJI NANGKA DAN TEPUNG AMPAS TAHU DALAM PEMBUATAN MI BASAH - SANDY GUSTIAWAN; NETTI HERAWATI; DEWI FORTUNA AYU (Universitas Riau, 2018)
This study aimed to get the best formulation and treatment of wet noodles from wheat flour with addition ofa combination of jackfruit seed and okara flour. The research was conducted with an experiment methodusing a completely randomized design with five treatments and three replications. Study on the treatment i.e.M1 (80% wheat flour : 20% jackfruit seed : 0% okara flour), M2 (80% wheat flour : 15% jackfruit seed : 5%okara flour), M3 (80% wheat flour :10% jackfruit seed : 10% okara flour), M4 (80% wheat flour : 5% jackfruitseed : 15% okara flour), and M5 (80% wheat flour : 0% jackfruit seed : 20% okara flour). Data werestatistically analized using Analysis of Variance and continued with Duncan’s New Multiple Range Test atlevel 5%. Results of the analysis showed that ratio of wheat flour with the addition of a combination ofjackfruit seed flour and okara flour significantly affected on ash content, crude fiber content, fat content,protein content, and carbohydrate content as well as descriptive and hedonic sensory test of the wet noodles.Based on this research, the best treatment was ratio of wheat flour, jackfruit seed, and okara flour80%:10%:10% which had moisture content 32.61%, ash content 0.67%, crude fiber content 5.30%, fatcontent 2.47%, protein content 3.94%, and carbohydrate content 60.29%. Characteristics of best treatmentof wet noodles based on descriptive test was less yelow, rather flavorful jackfruit seed, rather flavorful beany,and chewy texture.